ESC EORP Cardiomyopathy Registry: real‐life practice of genetic counselling and testing in adult cardiomyopathy patients. (7th August 2020) - Heliö, Tiina; Elliott, Perry; Koskenvuo, Juha W.; Gimeno, Juan R.; Tavazzi, Luigi; Tendera, Michal; Kaski, Juan Pablo; Mansencal, Nicolas; Bilińska, Zofia; Carr‐White, Gerry; Damy, Thibaud; Frustaci, Andrea; et al.
Abstract: Aims: Cardiomyopathies comprise a heterogeneous group of diseases, often of genetic origin. We assessed the current practice of genetic counselling and testing in the prospective European Society of Cardiology EURObservational Research Programme Cardiomyopathy Registry. Methods and results: A total of 3208 adult patients from 69 centres in 18 countries were enrolled. Genetic counselling was performed in 60.8% of all patients [75.4% in hypertrophic cardiomyopathy (HCM), 39.2% in dilated cardiomyopathy (DCM), 70.8% in arrhythmogenic right ventricular cardiomyopathy (ARVC), and 49.2% in restrictive cardiomyopathy (RCM), P < 0.001]. Comparing European geographical areas, genetic counselling was performed from 42.4% to 83.3% ( P < 0.001). It was provided by a cardiologist (85.3%), geneticist (15.1%), genetic counsellor (11.3%), or a nurse (7.5%) ( P < 0.001). Genetic testing was performed in 37.3% of all patients (48.8% in HCM, 18.6% in DCM, 55.6% in ARVC, and 43.6% in RCM, P < 0.001). Index patients with genetic testing were younger at diagnosis and had more familial disease, family history of sudden cardiac death, or implanted cardioverter defibrillators but less co‐morbidities than those not tested ( P < 0.001 for each comparison). At least one disease‐causing variant was found in 41.7% of index patients with genetic testing (43.3% in HCM, 33.3% in DCM, 51.4% in ARVC, and 42.9% in RCM, P = 0.13). Conclusions: This is the first detailed report on the real‐life practice of genetic counselling and testing in cardiomyopathies in Europe. Genetic counselling and testing were performed in a substantial proportion of patients but less often than recommended by European guidelines and much less in DCM than in HCM and ARVC, despite evidence for genetic background.